Academic advisors' record keeping andmonitoring system (AA-ReKeMoS) / Nik Zam Nik Wan ...[et al.] - Nik Wan, Nik Zam; Saidi, Noraida; Razak, Syuhaila; San, Suzana; Abu Bakar, Rosliza (2019)
-UiTM Academic Advisors or commonly known as 'Penasihat Akademik (PA)' are appointed among lecturers to be responsible for a group of students. PA is responsible to advice those students with regards to their academic planning, to monitor their academic activities as well as academic achievements. PA can play an important role in ensuring the students meet UiTM's academic objectives which include graduating on time with CGPA more than 3.00. However, due to demanding schedule of PA as lecturers, they seem to be having lack of time to schedule meetings with the students and unsystematic recording of PA-students meetings will make monitoring almost impossible. Consequently problematic as well as weak students cannot be identified sooner for appropriate actions leading to poor academic performance that would affects faculty's overall performances. Therefore, Academic Advisors' Record Keeping and Monitoring System (AA- ReKeMoS) is necessary to enable PA- students' activities to be frequently updated and the information can be made accessible to Head of Faculty for monitoring purposes. Apart from monitoring individual PA's activities, Head of Faculty can also obtain information about each student from the system. AA-ReKeMoS is cheap, manageable and can be widely applied since it utilized Microsoft Excel and Google Drive that can be easily accessed and are free for all the Academic Advisors.